Emotions and epistemology: a path for reconsideration in the 21st century - Scribano, Adrián Oscar (2017)
The present paper explores the gap between sensations and emotions in the global capitalism. We held the thesis that there are diverse ways to systematise the theoretical orientations on which the studies on the body/emotion are based; a possible one, having in mind the Latin American context and without intent of exhaustiveness, is the following: a) a line of work connected to Foucault and his concepts of control, discipline, and technologies of the self; b) an approach connected to Bourdieu and his notions of habitus, body hexis, and social fields; c) a set of investigations in the field of biopolitics referring to Esposito and Agamben on the one hand, and to Negri and Hardt on the other; and d) the investigations that, from a post-colonial vision, take up corporality on a track toward anti-hegemonic thought.